2018
DOI: 10.1111/jcal.12298
|View full text |Cite
|
Sign up to set email alerts
|

The effect of web‐based education on the self‐confidence and anxiety levels of paediatric nursing interns in the clinical decision‐making process

Abstract: This study was conducted to investigate the effect of web-based teaching on paediatric nursing internship students' self-confidence and anxiety levels in the clinical decision-making process. The study sample consisted of 61 students who received internship training in the Pediatric Nursing department. There were 30 students in the control group and 31 students in the experimental group. Data were collected using a sociodemographic form, and nursing anxiety and self-confidence levels were measured using a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…Other challenges included anxiety, students' mental distraction, monitoring attendance online, and assessing homework or assignments. These findings corroborate results from earlier studies, for example, anxiety in web-based education (Bektas & Yardimci, 2018), attendance and absenteeism during recorded online lecture videos (Trenholm et al, 2019), cheating and the credibility of unsupervised exams in asynchronous online environments (Feinman, 2018;Sullivan, 2016) and the need for formative assessment (Liberman et al, 2020;Wiliam, 2018).…”
Section: Rq3: What Are the Issues And Challenges Faced By Educators When They Make The Transition To Emergency Remote Instruction?supporting
confidence: 88%
See 1 more Smart Citation
“…Other challenges included anxiety, students' mental distraction, monitoring attendance online, and assessing homework or assignments. These findings corroborate results from earlier studies, for example, anxiety in web-based education (Bektas & Yardimci, 2018), attendance and absenteeism during recorded online lecture videos (Trenholm et al, 2019), cheating and the credibility of unsupervised exams in asynchronous online environments (Feinman, 2018;Sullivan, 2016) and the need for formative assessment (Liberman et al, 2020;Wiliam, 2018).…”
Section: Rq3: What Are the Issues And Challenges Faced By Educators When They Make The Transition To Emergency Remote Instruction?supporting
confidence: 88%
“…The problematic aspects of remote or distance education have been identified by researchers, for example students' and teachers' anxiety in web-based learning environments (Bektas & Yardimci, 2018), as well as lack of presence when recorded lecture videos are used (Trenholm et al, 2019). However, the phenomenon of cheating when students are not supervised during asynchronous online tests (Feinman, 2018;Sullivan, 2016) and and lack of formative assessments (Liberman, Levin, & Luna-Bazaldua, 2020;Wiliam, 2018) are seen as the most challenging aspects of remote or distance education.…”
Section: Challenges Presented By Emergency Remote Instructionmentioning
confidence: 99%
“…Recent research has shown that, experiencing online learning anxiety significantly affects academic achievement (Ajmal & Ahmad, 2019 ; Saadé et al, 2017 ) even though web-based and online learning might benefit some students (especially those with social anxiety or anxiety disorders) by decreasing the levels of perceived stress (Bektaş & Yardımcı, 2018 ; Keskin et al, 2020 ). One possible reason is the tight relationship between anxiety and the use of Internet or technology (computer anxiety) as explained in Saadé et al ( 2017 ), as well as the fact that students’ computer related self-efficacy has a significant effect on their experienced anxiety in online learning environments (Heckel & Ringeisen, 2019 ; Hill et al, 2009 ; Saadé & Kira, 2009 ).…”
Section: Measures Selection and Research Hypothesesmentioning
confidence: 99%
“…Bu bulgu literatür ile de uyumludur. Literatürde de klinik karar vermede özgüven düzeyinin uzun dönemde bilginin artması ve klinik deneyim ile birlikte geliştiği, öğrencinin yaşadığı olumlu deneyimlerin ve olumlu rol modellerin özgüven düzeyini arttırdığı vurgulanmaktadır (23,25,31) . Özellikle son yıllarda artan öğrenci sayısı, öğretim elemanı başına düşen öğrenci sayısının fazlalığı, klinik alanların yetersizlikleri, zaman olarak staj sürelerinin yeterli olmasına rağmen, fazla öğrenci sayısı nedeni ile bakılan hasta sayısının düşmesi, öğretim elemanlarının öğrenciye ayırdığı zamanının azalması bu çalışmada klinik stres ve anksiyetenin klinik karar vermede özgüven düzeyini düşük düzeyde etkilemesine yol açtığı düşünülmektedir (32,33) .…”
Section: Discussionunclassified